On-line monitoring of dissolution processes in nonaqueous electrolytes – A case study with platinum - Ranninger, Johanna; Wachs, Susanne; Möller, Jonas; Mayrhofer, Karl; Berkes, Balázs B. (Electrochemistry Communications, 2020)
Fundamental understanding of electrochemistry in nonaqueous electrolytes is important for applications like nonaqueous batteries, electroorganic synthesis, CO2 reduction, or metal deposition. Studies on electrode stability contribute to our fundamental understanding and are essential for the evaluation of the overall performance of electrochemical systems. With this work we introduce a tool to this field aiming to particularly investigate dissolution of different electrode materials qualitatively and quantitatively in water-free, organic media. The new approach consists of an electroanalytical flow cell with scanning capability on-line coupled to an inductively coupled plasma mass spectrometer, all together optimized to harsh organic environments. As a case study to demonstrate the strength of the method, we have chosen platinum as working electrode. We unveil its dissolution behavior in methanol-based organic electrolytes for the first time under controlled atmosphere (glovebox), and demonstrate differences in dissolution mechanism compared to aqueous electrolytes.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Anodic dissolution; Methanol-based electrolyte; Nonaqueous electrochemistry; On-line dissolution monitoring; Organic ICP-MS; Platinum dissolution